Hybrid Paper and 3D-Printed Microfluidic Device for Electrochemical Detection of Ag Nanoparticle Labels - Walgama, Charuksha (Lab Chip, 2020)
In the present article we report a new hybrid microfluidic device (hyFlow) comprising a disposable paper electrode and a three-dimensional (3D) printed plastic chip for the electrochemical detection of a magnetic bead-silver nanoparticle (MB-AgNP) bioconjugate. This hybrid device evolved due to the difficulty of incorporating micron-scale MBs into paper-only fluidic devices. Specifically, paper fluidic devices can entrap MB-containing conjugates within their cellulose or nitrocellulose fiber matrix. The hyFlow system was designed to minimize such issues and transport MB conjugates more efficiently to the electrochemical detection zone of the device. The hyFlow system retains the benefit of fluid transport by pressure-driven flow, however, no pump is required for its operation. The hyFlow device is capable of detecting either pre-formed MB-AgNP conjugates or conjugates formed in-situ formation. The detection limit of AgNPs using this device is 12 pM, which represents just 22 AgNPs per MB.